Are existing self‐ratings of acute manic symptoms in adults reliable and valid?—A systematic review. (13th April 2020) - Meyer, Thomas D.; Crist, Nicholas; La Rosa, Nikki; Ye, Biyu; Soares, Jair C.; Bauer, Isabelle E.
Abstract: Background: Depression research historically uses both self‐ and clinician ratings of symptoms with significant and substantial correlations. It is often assumed that manic patients lack insight and cannot accurately report their symptoms. This delayed the development of self‐rating scales for mania, but several scales now exist and are used in research. Our objective is to systematically review the literature to identify existing self‐ratings of symptoms of (hypo)mania and to evaluate their psychometric properties. Methods: PubMed, Web of Knowledge, and Ovid were searched up until June 2018 using the keywords: "(hypo)mania, " "self‐report, " and "mood disorder" to identify papers which included data on the validity and reliability of self‐rating scales for (hypo)mania in samples including patients with bipolar disorder. Results: We identified 55 papers reporting on 16 different self‐rating scales claiming to assess (hypo)manic symptoms or states. This included single item scales, but also some with over 40 items. Three of the scales, the Internal State Scale (ISS), Altman Self‐Rating Mania Scale (ASRM), and Self‐Report Manic Inventory (SRMI), provided data about reliability and/or validity in more than three independent studies. Validity was mostly assessed by comparing group means from individuals in different mood states and sometimes by correlation to clinician ratings of mania. Conclusions: ASRM, ISS, and SRMI are promising self‐rating tools for (hypo)mania to be used in clinical contexts. Future studies are, however, needed to further validate these measures; for example, their associations between each other and sensitivity to change, especially if they are meant to be outcome measures in studies.